18-year survival of posterior composite resin restorations with and without glass ionomer cement as base. Issue 6 (June 2015) - van de Sande, Françoise H.; Da Rosa Rodolpho, Paulo A.; Basso, Gabriela R.; Patias, Rômulo; da Rosa, Quéren F.; Demarco, Flávio F.; Opdam, Niek J.; Cenci, Maximiliano S.
Highlights: We assessed the 18-year survival of posterior resin composite restorations. We examined the influence of having GIC as base on restoration survival. Regarding type of failures, more fractures were seen when a base was present. Annual failure rates were similar (∼2%) for restoration with or without bases. The long-term survival of restorations was not affected by the use GIC as base. Abstract: Objective: Advantages and disadvantages of using intermediate layers underneath resin-composite restorations have been presented under different perspectives. Yet, few long-term clinical studies evaluated the effect of glass-ionomer bases on restoration survival. The present study investigated the influence of glass-ionomer-cement base in survival of posterior composite restorations, compared to restorations without base. Methods: Original datasets of one dental practice were used to retrieve data retrospectively. The presence or absence of an intermediate layer of glass-ionomer-cement was the main factor under analysis, considering survival, annual failure rate and types of failure as outcomes. Other investigated factors were: patient gender, jaw, tooth, number of restored surfaces and composite. Statistical analysis was performed using Fisher's exact test, Kaplan–Meier method and multivariate Cox-regression. Results: In total 632 restorations in 97 patients were investigated. Annual failure rates percentages up to 18-years were 1.9% and 2.1% for restorations with and without base, respectively. In restorations with glass-ionomer-cement base, fracture was the predominant reason for failure, corresponding to 57.8% of total failures. Failure type distribution was different ( p = 0.007) comparing restorations with and without base, but no effect in the overall survival of restorations was found ( p = 0.313). Significance: The presence of a glass-ionomer-cement base did not affect the survival of resin-composite restorations in the investigated sample. Acceptable annual failure rates after 18-years can be achieved with both techniques, leading to the perspective that an intermediate layer, placed during an interim treatment, may be maintained without clinical detriment, but no improvement in survival should be expected based on such measure.